Rescue extracorporeal life support as a bridge to durable left ventricular assist device. Issue 4 (April 2022) - Zubarevich, Alina; Zhigalov, Konstantin; Szczechowicz, Marcin; Arjomandi Rad, Arian; Vardanyan, Robert; Torabi, Saeed; Papathanasiou, Maria; Luedike, Peter; Koch, Achim; Pizanis, Nikolaus; Kamler, Markus; Schmack, Bastian; et al.
Background: The ideal timing of a durable assist device implantation in patients with end-stage heart failure presenting with INTERMACS profile I is still controversial. The data on extracorporeal life support (ECLS) bridge to durable left ventricular assist device (LVAD) in these patients is limited. Materials and methods: We retrospectively analyzed the outcomes of 35 patients in acute cardiogenic shock (CS) who, between December 2013 and September 2020, were bridged with ECLS to durable LVAD. The mean age was 52.3 ± 12.0 years. The primary endpoints of this study were in-hospital, 30-day, 6-month, and 1-year mortality. The secondary endpoint was the development of any postoperative adverse events and other characteristics during the follow-up period. We also assessed the impact of the rescue ECLS on the recovery of the end-organ function. Results: In-hospital, 30-day, 6-month, and 1-year survival was 65.6%, 75.9%, 69.2%, and 62.7% respectively. The median time on ECLS was 7 days (IQR 5.0–13.0). We observed a high incidence of a severe right heart failure (22.9%), acute kidney injury on dialysis (68.6%), and respiratory failure (77.1%). Bridge with ECLS provided a significant recovery of liver and kidney function prior to durable LVAD implantation. Conclusion: The concept of bridging patients presenting in end-stage heart failure and cardiogenic shock with ECLS prior to durable LVAD implantation is a feasible method to ensure acceptable survival rates and significant recovery of the end-organ function.